Sistem Informasi Administrasi Keuangan Kencleng Masjid Akbar Guli Lor Berbasis Web - Rifan Ardyansyah; Khanun Roisatul Ummah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Masjid Akbar Guli Lor functions as a center for religious and social activities within the community. However, its kencleng (charity box) program faces challenges in financial administration, including inaccurate reports and poorly recorded congregation data. This study aims to develop an integrated financial administration information system for the kencleng program to improve accessibility and transparency of donation funds. The method used is the System Development Life Cycle (SDLC) with a waterfall model approach, consisting of requirement analysis, design, implementation, testing, and maintenance phases. The system is built using the PHP programming language with the Laravel framework. Testing was conducted using black box and System Usability Scale (SUS) methods. The black box testing results show that all system functions operate according to the design. Meanwhile, the SUS test involving 30 respondents recorded an average score of 77,25, which falls under the